Sb-doped Tl8.67 Sn1.33-xSbx Te6 nanoparticles improve power factor and electronic charge transport - Khan, Sabir; Shah, Wiqar H.; Tufail, M.; Ali, Akhtar; Eldin, Sayed M.; Imran, Naveed; Sohail, Muhammad (Frontiers in Materials, 2023)
Sb (with different concentration ratios i.e 0.63, 0.65, 0.66, 0.68, 0.70, 0.72) doped Tellurium Telluride Tl8.67 Sn1.33-xSb¬xTe6 nano compound was prepared by solid state techniques and the compound was heated up to 550 K in vacuum silica tube. The structure of nano system was studied by using XRD and EDX, through which it was confirmed that without any other impurities the nano system as single-phase tetragonal crystal structure. The measured “S” of all nano compounds shows that by increasing the temperature i.e. (from 300 to 550 K), S also increases. Seebeck coefficient(S) shows positive for all temperatures, by showing characteristics of p-type semiconductor. The complex behaviour of Seebeck coefficient (S) for Sb doped nano system observed that at low temperature i.e room temperature, first the Seebeck coefficient (S) decreases with increase in Sb concentration up to x=0.65, and then Seebeck coefficient (S) increases with the increasing in Sb dopent up to x= 0.72. Similarly also electrical conductivity (σ) decreases with the increases temperature, also the power factors shoes the complex behaviour with the concentrations of Sb. The PF (S2σ) observed for Tl8.67 Sn1.33-xSb¬x Te6 nano compound changes (increases) with increase in the temperature range of i.e. (300-550) K. Telluride’s are semiconductors of very narrow band-gap, all of its elements are in common oxidation states, according to (Tl+9) (Sb3+) (Te2-)6. The Phases range was also checked out and found that different dopant ratio of ‘Sb’ can also changes the properties i.e electrical and thermal of the nano system